(untitled) (Journal of Decolonising Disciplines, 2021)
I am interested in a decolonial reading of African vernacular rooted sculptures of selected contemporary South African and Nigerian artists and compares them. Although vernacular arts were produced in indigenous or traditional African arts context, there are still several forms of vernacular art practices jostling for space with canonical modes in contemporary art in various African contexts. However, I argue that the contemporary representations of cultural imagery and symbols from indigenous cultures or urban areas in South Africa and Nigeria suggest a different mode of engagement, even though the term vernacular is used to narrate them as a rethink in narrating art practices. Therefore, my paper argues that even though contemporary artists from both countries continue to represent cultural imagery (vernacular) in their artworks, they are not a continuation of traditional African art. I adopt formal analysis, cultural history methodologies for the critical analysis of the works of two South African and two Nigerian artists that were purposively selected and compare the ideas that unfold from the interrogations for a wider continental understanding of contemporary issues and artistic trends.